A collective education mentorship model (CEMM): Responding to the TRC calls to action in undergraduate Indigenous health teaching - Yeung, Sharon; Ge, Yipeng; Shanbhag, Deepti; Liu, Alex; Downey, Bernice; Hill, Karen; Martin-Hill, Dawn; Amster, Ellen; McKnight, Constance; Wahi, Gita (International Journal for Students as Partners, 2020)
In this paper, a Collective Education Mentorship Model (CEMM) is described by four non-Indigenous students who co-created and undertook a program with this model for an undergraduate-level university experiential learning experience centred around Indigenous health. This model is framed around shared teaching of students by various collaborators/mentors and built upon the values of collaboration, mentorship, reciprocity, and capacity building. Based on feedback from the students and collaborators involved in this experience, this model appears to be a promising means of better situating students as partners in experiential learning through the redefinition of student-supervisor roles, responsibilities, and the sharing of power. Furthermore, this model appeared to create more diverse experiences for students and minimized supervisor burden. Although this model was created specifically for the education of trainees in Indigenous health, it can be further adapted for other student placements and programs where these assets would be beneficial.